PEMBERDAYAAN IRT PRODUSEN TAHU DI SUDAGARAN, KOTA YOGYAKARTA - Adi Soeprapto; Didik Indarwanta; Sadeli Sadeli; Indro Herry Mulyanto; Susanta Susanta; Keny Rahmawati (Dharma: Jurnal Pengabdian Masyarakat, 2022)
Small, Micro and Medium Enterprises (MSMEs) face quite complex problems in business development. One of the small businesses engaged in by the Sudagaran community in Yogyakarta is the production of tofu. Entrepreneurs know problems in the fields of production, environment, capital, and also marketing. The Service Team from the Department of Business Administration, FISIP UPN Veterans Yogyakarta collaborated with the Yogyakarta City Baznas and the Yogyakarta City Government to assist and assist SMEs. Empowerment programs that have been carried out have started from the implementation of production layouts, small business financial management, simple financial records, product innovation. packaging, and online-based marketing. Small entrepreneurs feel helped by the service program so that during the Covid-19 pandemic they have alternatives in product marketing.